Study of Issues of Classification, Description, Recognition, Evaluation and Accounting of Finished Products Created in Cotton-Textile Clusters (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The cotton and textile industry is one of the most important sectors of the domestic economy, acting as a driver for regional development, creating production capacities in rural areas, providing employment, and increasing export volumes. Therefore, on the initiative of the head of our state, at the new stage of reforms, the cotton-textile front was radically updated and a cluster system was introduced.